(untitled) (Hematology Meeting Reports, 2009)
The biologic, clinical and therapeutic setting is nowadays such that risk factors are constantly changing and progressively increasing in patients suffering from different onco-hematological conditions. In addition to situations that are well known or that are gradually being recognized related both to the underlying disease and to treatment, such as neutropenia, neutrophil dysfunction, mucosal damage, concomitant monocytopenia and lymphopenia, abnormalities within the host cellular and humoral compartments, impairments in cytokine networks, alterations in T lymphocytes/tumor interactions, crosstalks between neoplastic cells and accessory cells, etc, over the last few years we are witnessing important changes in the overall management of patients with acute and chronic hematological malignancies.